The Interplay Between Economic Diversification, Foreign Direct Investment, and Climate Change in Saudi Arabia - Louail Bilal; Riache Siham; Alanazi Yazeed Mohammed (Civil and Environmental Engineering)
This study examines the short-run and long-run repercussions of export diversification and foreign direct investment on climate change and greenhouse gas emissions in Saudi Arabia. In addition, the specification includes gross domestic product, total energy use, and urbanization as control variables. The outcomes of the study are as follows. First, the ARDL model provides empirical evidence supporting long-run cointegrating relationships among the variables. Second, export diversification, gross domestic product, and urbanization increase greenhouse gas emissions in the short-run and long-run. Nevertheless, the long-run adverse consequences of these variables tend to be greater than their short-run effects. Third, foreign direct investment inflows reduce greenhouse gas emissions and enhance short- and long-run environmental conditions. Finally, energy use has no significant impact on environmental conditions. These conclusions are robust against many empirical issues, including autocorrelation, heteroskedasticity, misspecification, and normality. The cumulative sum of recursive residuals and cumulative sum of recursive residuals of squares plots confirm the stability of long-run parameters and the validity of the ARDL estimations. The findings offer significant perspectives on measures that should be taken to preserve the environment.